Development of Peace Education Modules through Problem-Based Learning to Improve Women's Conflict Resolution Skills - Taufik, Taufik; Nur Aini; Ruwaidah; Nurwahidah, Nurwahidah (Universitas Islam Negeri (UIN) Jurai Siwo Lampung, 2025)
This study aimed to develop a peace education module based on Problem-Based Learning (PBL) to strengthen students’ conflict-resolution skills, particularly female students, at STKIP Taman Siswa Bima. The research employed the ADDIE model of Research and Development (R&D). The participants consisted of 90 students for the needs analysis and 30 purposively selected students for a limited trial. Data were collected through needs questionnaires, expert validation, practicality tests, classroom observations, authentic assessments, and pre-/post-tests of conflict-resolution skills. The findings revealed that the module achieved an average expert validation score of 4.45 (very valid) and a practicality score of 4.4 (very practical). Classroom observations resulted in an average score of 4.34 (very good), while authentic assessments of conflict-resolution skills reached an average of 4.34 (87%), categorized as very good. Effectiveness testing showed a significant improvement in conflict-resolution skills, increasing from M = 65.9 (SD = 8.7) at the pre-test to M = 78.8 (SD = 7.8) at the post-test, *t*(29) ≈ 6.5, *p* < 0.001, Cohen’s *d* ≈ 1.1 (large effect size). In conclusion, the PBL-based peace education module, which integrates the local cultural values of *Maja Labo Dahu* and moderate Islam, is valid, practical, and effective in enhancing students’ conflict-resolution skills. The module is recommended for broader implementation across study programs and community service activities as a tangible contribution to strengthening peace education in higher education. Keywords: Module; Peace Education; Problem-Based Learning; Conflict Resolution; Moderate Islam.